Połączenie programowania celowego ze zrównoważoną kartą wyników - Kuchta, Dorota; Ryńca, Radosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the paper the idea of balanced scorecard is presented emphasising the aspect of balancing of various aspects and perspectives. Then basic information about goal programming is given, where the accent is put on the way various goals are treated. The notion of unfavourable deviation from the desired values is presented and then it is shown how the unfavourable deviations are minimised taking into account, in a balanced way, all the goals and their priorities. Next it is shown how the idea of goal programming can be helpful in controlling the balance in the balanced scorecard. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 181-189